THE FIRST FEMALE CHEMIST (AND PHARMACIST?) IN JAPAN: CHIKA KURODA - VALDÉS, JUAN NÚÑEZ VALDÉS (International Journal of Multidisciplinary Research and Studies, 2022)
This paper follows a line of research started some time ago by the author with the purpose of presenting to society the biographies of women who managed to overcome the prejudices and laws in force of the time in which they lived, which prevented them from carrying out university studies to different from what happened at the same time with men. The main objective is to show the biography of Chika Kuroda, the first woman to obtain a degree in Chemistry in Japan, in the first decades of the last century and also the second woman to get a Ph.D. in Science in 1929 (some sources point out that she was also pharmacist, although this fact is not properly documented). The methodology used has been the search for data on this woman in bibliographical and computer sources, as well as in historical archives. As a main result, a biography of her, as complete as possible, has been constructed. Some brief biographical data on her compatriot Kono Yasui, the first Japanese woman to receive the degree of doctor in Science are also shown.